Multilevel Collapsibility of Loess under Irrigation in Jinya Town, Gansu Province, China - Xiaozhou Zhang; Yudong Lu; Xin Li; Yangchun Lu; Jianzhong Sun; Wangsheng Pan (Advances in Civil Engineering)
The collapsibility of loess has constantly been a major problem in engineering geology. The determination of the collapsibility process and characteristics of loess are crucial to foundation construction and residents’ life in the Loess Plateau. Thus, a large-scale in situ irrigation collapse experiment was conducted on a 10 m2 test pit. A total of 79 benchmarks are used in this experiment. These benchmarks are divided into three categories, namely, deep-buried steel pipe benchmarks, ground benchmarks inside the pit, and ground benchmarks outside the pit. The irrigation and observation time spanned 40 days. In the entire irrigation experiment, a three-day water suspension period resulted in two peaks on the collapsibility velocity curve, thereby showing a remarkable difference in the collapsibility curve from the standard one. In terms of the microstructural deformation types of loess and infiltration process of irrigation water, we found that the collapsibility of loess is a dynamic process apart from being particularly sensitive to water. That is, even after a full collapse of the irrigation process, new pores will eventually form once the water content in the loess begins to decline, thereby providing conditions for another loess collapse. Therefore, multilevel collapsibility can occur during continuous irrigation, which is a problem that has been unexplored in previous applications.